ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, PROMOSI, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Floo Cafe Ungaran) - Saputro, Arianto; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2016)
This research was done because of a decline in sales on the Floo Cafe for several months in a row, so keep in mind the factors that influence the purchase decision. This study aims to determine the effect of the perception of price, quality of service, promotion, and location of the purchase decisions on the Floo Cafe and which ones have the most influence on purchasing decisions on the Floo Cafe.The research data was collected from 100 consumers Floo Cafe. Pengambilan sample in this study using a non-probability sampling techniques. The analysis used in this research is multiple regression analysis. Previous test the validity and reliablitas and classical assumption. After multiple regression analysis to test the hypothesis and the coefficient of determination. The results of a study reported the following regression equation: Y = 0,190Â + 0,587Â + 0,273Â + 0,166.Regression analysis showed perception variables of price, quality of service, promotion and location has a positive influence on purchase decisions. The variable that has the most impact is the quality of service, followed by promotions and price perception, while having little effect most is the location. The results of the analysis using t test showed that the quality of service, price perception prmosi and individually have a significant influence on purchasing decisions. This equation models have a value of 72.610 with a significance level of 0.000. The results of the analysis by using the coefficient of determination indicated that about 74.3% of the purchase decision can be explained by the perception of price, quality of service, promotion, and location while 25.7% is explained by other variables that are not described in this study.